Development of a Mosquito Repellent Formulation Based on Nanostructured Lipid Carriers - Abrantes, Daniele Carvalho; Rogerio, Carolina Barbara; de Oliveira, Jhones L.; Campos, Estefânia V. R.; de Araújo, Daniele Ribeiro; Pampana, Laurindo Cesar; Duarte, Marcelo José; Valadares, Geórgio Freesz; Fraceto, Leonardo Fernandes (Frontiers in Pharmacology, 2021)
Arboviral diseases are a threat to global public health systems, with recent data suggesting that around 40% of the world’s population is at risk of contracting arboviruses. The use of mosquito repellents is an appropriate strategy to avoid humans coming into contact with vectors transmitting these viruses. However, the cost associated with daily applications of repellents can make their use unfeasible for the low-income populations that most need protection. Therefore, the development of effective formulations offers a way to expand access to this means of individual protection. Consequently, research efforts have focused on formulations with smaller quantities of active agents and sustained release technology, aiming to reduce re-applications, toxicity, and cost. The present study investigates the development of nanostructured lipid carriers (NLCs) loaded with a mixture of the compounds icaridin (synthetic) and geraniol (natural), incorporated in cellulose hydrogel. The NLCs were prepared by the emulsion/solvent evaporation method and were submitted to physicochemical characterization as a function of time (at 0, 15, 30, and 60 days). The prepared system presented an average particle size of 252 ± 5 nm, with encapsulation efficiency of 99% for both of the active compounds. The stability profile revealed that the change of particle size was not significant (p >0.05), indicating high stability of the system. Rheological characterization of the gels containing NLCs showed that all formulations presented pseudoplastic and thixotropic behavior, providing satisfactory spreadability and long shelf life. Morphological analysis using atomic force microscopy (AFM) revealed the presence of spherical nanoparticles (252 ± 5 nm) in the cellulose gel matrix. Permeation assays showed low fluxes of the active agents through a Strat-M® membrane, with low permeability coefficients, indicating that the repellents would be retained on the surface to which they are applied, rather than permeating the tissue. These findings open perspectives for the use of hybrid formulations consisting of gels containing nanoparticles that incorporate repellents effective against arthropod-borne virus. These systems could potentially provide improvements considering the issues of effectiveness, toxicity, and safety.